The Importance of Antibiotic Treatment in Cardiovascular Patients with Periodontal Disease - Saghin, Alina; Lazar, Aurel; Lazar, Liviu; Rus, Marius (Medicine and Pharmacy Reports, 2014)
In the last three decades many studies have found that subjects with periodontal disease and multiple tooth extractions due to chronic advanced periodontal disease, present a higher risk of developing cardiovascular disease than those with no or low levels of periodontal infection. The main objective of the study is to determinate the comparative effects of dental procedures in marginal chronic periodontitis (associated with low or solitary doses of antibiotics), the coronary atherosclerotic disease relationship, and the specific management. Conclusions: 1. Dental procedures associated with antibiotic treatment was superior to simple procedural treatment, in all patients involved. 2. Periodontal infection control could lead to lower levels of inflammation markers and markers of systemic endothelial dysfunction. To the extent in which periodontal infection control decreases the incidence of coronary atherosclerotic cardiovascular events it may be assumed that the dental management of cardiovascular disease is in progress.